TECHNOLOGIES OF SURFACE STRENGTHENING OF GEARS AND BEARINGS IN OIL WITH AN ADDITIVE OF FLUORINE GRAPHITE - Kindrachuk, Myroslav; Leusenko, Darya; Melnyk, Volodymyr; Vasylyk, Mykhailo; Kharchenko, Volodymyr (Problems of Friction and Wear, 2024)
The results of research and testing of the technology of strengthening contact surfaces in an oil medium with the addition of fluorinated graphite of the teeth of bevel gears and rolling bearings are presented. The technology provides a significant increase in resource by slowing down the development of fatigue damage to the teeth of bevel gears and rolling bearings of the NK-14ST engine starter drive.